2001
DOI: 10.1183/09031936.01.17303370
|View full text |Cite
|
Sign up to set email alerts
|

Dose dependent increased mortality risk in COPD patients treated with oral glucocorticoids

Abstract: Systemic corticosteroids are often administered in COPD patients. The relationship between systemic glucocorticoids and mortality in patients with moderate to severe chronic obstructive pulmonary disease (COPD) was retrospectively analysed. Baseline characteristics of the patients, in stable clinical condition, were collected on admission to a pulmonary rehabilitation centre. Overall mortality was asessed at the end of follow-up. The Cox proportional hazards model was used to quantify the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
12

Year Published

2003
2003
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 21 publications
1
49
1
12
Order By: Relevance
“…The study of STROM [32] showed that oral corticosteroids were associated with increased risk of hospitalisation in females but not in males. In the study of SCHOLS et al [33], oral corticosteroid therapy in moderate-to-high doses was associated with increased mortality risk but only in the absence of concomitant inhaled steroid therapy. When combined with inhaled corticosteroids, oral steroid therapy, even at high doses, did not significantly increase the mortality rate [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of STROM [32] showed that oral corticosteroids were associated with increased risk of hospitalisation in females but not in males. In the study of SCHOLS et al [33], oral corticosteroid therapy in moderate-to-high doses was associated with increased mortality risk but only in the absence of concomitant inhaled steroid therapy. When combined with inhaled corticosteroids, oral steroid therapy, even at high doses, did not significantly increase the mortality rate [33].…”
Section: Discussionmentioning
confidence: 99%
“…In the study of SCHOLS et al [33], oral corticosteroid therapy in moderate-to-high doses was associated with increased mortality risk but only in the absence of concomitant inhaled steroid therapy. When combined with inhaled corticosteroids, oral steroid therapy, even at high doses, did not significantly increase the mortality rate [33]. Although it is evident that oral corticosteroids are fraught with many serious adverse effects, they may also produce some clinical benefits [34], particularly in the short term.…”
Section: Discussionmentioning
confidence: 99%
“…The same group showed no benefit with the addition of 5 mg of prednisolone daily to inhaled corticosteroids in patients with relatively mild COPD in terms of decreasing the frequency or duration of AECB over a twoyear period (350). This, combined with the recognition of the significant complications of chronic oral corticosteroid therapy (351,352) including a dose-dependent increase in mortality (353), argues against chronic use of systemic steroids in COPD (Level II evidence). It appears that even patients on chronic oral corticosteroids can be weaned off this medication without any adverse effects on pulmonary function, quality of life or frequency of AECB (354).…”
Section: Prevention Of Aecbmentioning
confidence: 99%
“…However, practice surveys found that in COPD, ICS are frequently prescribed in situations that do not fit this indication [17]. Finally, long-term treatment with oral glucocorticosteroids is not recommended for the treatment of patients with COPD: no obvious beneficial effect has been described with these agents, which can have many deleterious consequences, including impairments in bone density, nutritional status and peripheral muscle function, aggravation of comorbid diseases, lessening of the efficacy of pulmonary rehabilitation and even decreased survival [1,18].…”
Section: Overview Of Current Treatment For Copdmentioning
confidence: 99%